INVESTIGATING UNDERGRADUATE STUDENTS’ PERCEPTIONS OF EXTENSIVE READING TOWARD THEIR VOCABULARY MASTERY IN ENGLISH DEPARTMENT OF PATTIMURA UNIVERSITY AMBON - Rosina F. J. Lekawael; Marcy S. Ferdinandus (University of Kuningan, 2021)
Reading is one of the critical skills in learning English in which students can develop their cognition, build vocabulary, as well as bring enjoyment. Extensive reading is known as one of the useful approaches to build students’ vocabulary repertoires by engaging students to read as much as they can be based on their appropriate reading level. Therefore, this survey study aims to find out how the students perceive their reading experiences in the extensive reading, how this approach increases their English vocabulary, as well as their reading comprehension. For the data collection technique, we distributed questionnaires for 40 undergraduate students in their second and fourth semester in the English department. To gain more comprehensive data, we also interviewed 20 students. The results of this study revealed that the majority of students show their positive response to and perception of extensive reading. We also found that this approach impacts the progress of students’ reading comprehension as well as the development of their vocabulary building. The findings of this study shed light on students’ perceptions of extensive reading and how it impacts their vocabulary building and reading comprehension. This study prompts further studies to examine the effectiveness of extensive reading on vocabulary learning of English foreign language students in various reading levels.